2004
DOI: 10.1103/physrevlett.92.166601
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Superparamagnetism and Anomalous Hall Effect in Highly Reduced Cobalt-Doped RutileTiO2δFilms

Abstract: We report a detailed magnetic and structural analysis of highly reduced Co doped rutile TiO 2-δ films displaying an anomalous Hall effect (AHE). The temperature and field dependence of magnetization, and transmission electron microscopy clearly establish the presence of nano-sized superparamagnetic cobalt clusters of ~8-10 nm size in the films at the interface. The co-occurrence of superparamagnetism and AHE raises questions regarding the use of the AHE as a test of the intrinsic nature of ferromagnetism in di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
200
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(213 citation statements)
references
References 22 publications
9
200
2
2
Order By: Relevance
“…43 for Co-doped ZnO nanoparticles and from those in Ref. 53 for highly reduced Co-doped TiO 2−␦ thin films, where the FC and ZFC curves diverge substantially at low temperatures. From the first three graphs, Figs.…”
Section: Magnetic Measurementsmentioning
confidence: 99%
“…43 for Co-doped ZnO nanoparticles and from those in Ref. 53 for highly reduced Co-doped TiO 2−␦ thin films, where the FC and ZFC curves diverge substantially at low temperatures. From the first three graphs, Figs.…”
Section: Magnetic Measurementsmentioning
confidence: 99%
“…There have also been a number of reports that ascribe the ferromagnetism to the Co segregation. 7,8,9 Strong evidence in support of intrinsic ferromagnetism has been given by the observations of anomalous Hall effect (AHE) and magnetic circular dichroism (MCD). 10,11,12,13,14 If the ferromagnetism were intrinsic, the charge carriers should be spin polarized due to the exchange interaction with the Co spins.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a secondary phase exists in the interface of TiO and its substrate for Co-doped TiO [13]. A crosssectional TEM sample was prepared for the x = 0.03 sample for such an investigation.…”
Section: Hrem Resultsmentioning
confidence: 99%